Rendering Reverence and Poetic Essence: A Comparative Critical Analysis of Hamza Yusuf, Shaykh Abdal Hakim Murad, Mostafa Azzam, and Aziza Spiker’s Translations of Qaseeda Burda - Bhatty, Shahzad Ahmad (Zoraiz, 2025)
This paper presents a comparative critical analysis of four prominent English translations of Qaseeda Burda by Imam al-Busiri. The translators Hamza Yusuf, Shaykh Abdal Hakim Murad, Mostafa Azzam, and Aziza Spiker each brings unique approaches to rendering this classical work of Islamic devotional poetry. The analysis is structured around key translation standards: fidelity to meaning, preservation of poetic form and rhythm, cultural sensitivity, accessibility, and emotional and spiritual resonance. Hamza Yusuf’s translation is noted for its theological precision and extensive commentary, making it suitable for readers seeking a deep contextual understanding. Shaykh Abdal Hakim Murad’s version stands out for its lyrical sophistication and balance between intellectual depth and poetic beauty. Mostafa Azzam’s translation emphasizes rhythm and melody, preserving the performative essence of Qaseeda Burda for recitative and musical traditions. Aziza Spiker’s rendition combines poetic elegance with spiritual sensitivity, offering accessibility without compromising the poem’s devotional tone. This comparative study highlights how each translator navigates the challenges of rendering the poem’s rich spiritual content, intricate poetic form, and cultural nuances. The analysis underscores the translators’ varied methodologies in balancing reverence for the original text with the demands of linguistic and cultural adaptation, ensuring that Imam al-Busiri’s timeless ode continues to resonate across linguistic and cultural boundaries.